Internalisasi Nilai Menghargai Sesama dalam Meminimalisir Perilaku Bullying pada Pesantren Modern Kota Banda Aceh - Ardian, Irvan; Misnawati, Misnawati; Silahuddin, Silahuddin (Tadabbur: Jurnal Peradaban Islam, 2024)
This research aims to determine the internalization of the value of respecting others in minimizing bullying behavior in modern pesantren in Banda Aceh City (MTsS Darul Ulum and SMPIT Teungku Chiek Dibitai). The research method used is descriptive qualitative with a field research approach. The respondents of this study were the Principal, 4 Islamic Religious Education teachers, 2 Counseling Guidance teachers and 20 students. Data collection techniques using interviews, observation and documentation. The data analysis technique used the Miles and Huberman analysis model. The results showed that, (1) there are several factors that cause bullying behavior in students at MTsS Darul Ulum and SMPIT Teungku Chiek Dibitai, namely family factors, peer factors and mass media or social media factors. (2) there are various policies carried out by MTsS Darul Ulum and SMPIT Teungku Chiek Dibitai in living the value of respecting others in minimizing bullying behavior in students through learning activities in the classroom and learning activities outside the classroom, (3) the implementation of internalizing the value of respecting others in minimizing bullying behavior at MTsS Darul Ulum and SMPIT Teungku Chiek Dibitai is carried out through exemplary, (4) the implications of the results of internalizing the value of respecting others in minimizing bullying behavior at MTsS Darul Ulum and SMPIT Teungku Chiek Dibitai include fostering caring and empathetic attitudes towards others, having good manners towards others, and respecting every difference. This research is expected to provide theoretical and practical benefits, especially in dealing with bullying behavior in all educational institutions.